The miscellaneous works of Tobias Smollett : complete in one volume / with memoir of the author by Thomas Roscoe. - Smollett, T. (Tobias), 1721-1771. (Tufts University. Tisch Library., 2015)
New edition /illustrated by George Cruikshank.; 1 online resource (xl, 966 pages, 20 unnumbered leaves of plates) : illustrations, portrait.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.